The Impact of the Syrian Refugee Crisis on Firm Entry and Performance in Turkey - Akgündüz, Yusuf Emre; van den Berg, Marcel; Hassink, Wolter (Published by Oxford University Press on behalf of the World Bank, 2019)
We analyze how the Syrian refugee inflows into Turkey affected firm entry and performance. To estimate the causal effects, we use instrumental variables, difference-in-differences, and synthetic control methodologies. The results suggest that hosting refugees is favorable for firms. Total firm entry does not seem to be significantly affected. However, there is a substantial increase in the number of new foreign-owned firms. In line with the increase in new foreign-owned firms, there is some indication of growth in gross profits and net sales.